KELAYAKAN FLASH CARD PADA SUB MATERI PTERIDOPHYTA KELAS X SMA - Kartiani, Nurul Atikah; Syamswisna, Syamswisna; Wahyuni, Eko Sri (Jurnal Pendidikan dan Pembelajaran Khatulistiwa, 2019)
AbstractThis research aimed to know the feasibility of flash card media from the results of pteridophyta inventory in the Gunung Sari Singkawang as lesson media in sub-material pteridophyta in highschool and identifying the type of pteridophyta. The sampling technique used was purpossive sampling following contours of the mountain on an altitude 25 m above sea level, 225 m above sea level to a height of 330 m above sea level. The reasults found 14 species of pteridophyta that is Lepisorus longifolius, Pityrogramma calomelanos, Cyclosorus heterocarpus, Nephrolepis hirsutula, Lygodium scandens, Blechnum capense, Lygodium flexuotum, Drynaria quersifolia, Drymoglossum piloselloides, Nephrolepis biserata, Asplenium nidus, Taenitis blechnoides Stenochlaena palustris,and Davallia denticulata. Flash card media of pteridophyta was validated by five validators consisting of three highschool biology teachers and 2 biology lecturers from FKIP Untan. Based on the validatorâ€™s assessment, flash card media was be avowed as valid with CVR and CVI values of 1, that it was suitable to be used as a lesson media in studying sub-material pteridophyta in highschool.Â Keywords : Feasibility, Flash Card, Pteridophyta